"THEME : Etude numérique de pression de terre passive et active et l’effet du milieu sur la stabilité d’un écran de soutènement " - محمد نجيب, دويس; عبد الحق, عسكري; عبد الكريم, خلوط (University of El-Oued, 2022)
"Abstract : The objective of this thesis is the numerical analysis of the effect of the mechanical properties of the soil and the common boundary between the soil and the structure on the distribution of soil stresses and the numerical evaluation of the coefficients of passive and effective soil pressures using the program Flac2D in the presence of gonorrhea. Experiments on models in the laboratory clearly indicated that the instability of the bottom of the pits in the presence of water flow can occur not only due to the phenomenon of the rise of a mass of soil or the imbalance, but also from the decrease in the reverse thrust. The results indicate that the presence of seepage flow has an unfavorable effect on thes tability of the retaining wall by increasing theactive earth pressureand decreasingpassive earth pressure .It is also shown thatthe properties of the earthfriction angle, the dilation angle and the roughnessof the wallshave an influence on the pressures of the earths.The penetration depth increases the passive earth coefficient and has virtually no effect on active earth coefficient. . Keywords: numerical modeling, deep fossils, stability, barrier, infiltration. ""إن الهدف من هذه المذكرة هو التحليل العددي لتأثير الخصائص الميكانيكية للتربة و للحد المشترك بين التربة و الهيكل على توزيع ضغوط التربة و التقييم العددي لمعاملات ضغوط التربة السلبية و الفعالة باستعمال البرنامج Flac2D في تواجد السيلان. التجارب على نماذج في المخبر بينت بوضوح أن عدم استقرار قعر الحفر بوجود جريان للماء يمكن أن يحدث ليس فقط بسبب ظاهرة الارتفاع لكتلة من التربة أو عدم التوازن بل أيضا من تناقص قوة الدفع العكسي. تشير النتائج المتحصل عليها ان وجود المياه يؤثر سلبيا على استقرار الحاجز وذلك بزيادة قوة الدفع و انقاص القوة الساندة للحاجز كما بينت النتائج أيضا تأثر هذه القوى بخصائص التربة و الحاجز كما أثبت النتائج أن زيادة عمق الحاجز في التربة ليس له تأثير على قوى الدفع وله تأثير صغير على القوى الساندة . الكلمات المفتاحية: نمذجة رقمية، الحفريات العميقة، الاستقرار، حاجز، ترشح. "
مذكرات ماستر تخصص ري
Keywords: Keywords: numerical modeling, deep fossils, stability, barrier, infiltration; الكلمات المفتاحية: نمذجة رقمية، الحفريات العميقة، الاستقرار، حاجز، ترشح.